NGO’s role in a public-private partnership : assessment of environmental educational efforts on short term - Bondesson, Wictoria (SLU/Dept. of Economics, 2014)
Business is changing and so are society’s expectations. Companies are expected to take responsibility for their trade and the context they are operating in, by looking at socially, economically and environmentally aspects. Many companies handle it by implementing corporate social responsibility (CSR) to their line of action. This is often handled by collaborating with other organisations, such as non-governmental organisations. A popular form of alliance is public-private partnership (PPP): A for-profit and one non-profit organisation join hands for a common cause. The for-profit organisation can bring in financial muscles and a know-how of the business, while the non-profit organisation can bring in expertise on the chosen issue, goodwill and legitimacy. Top managers have voted CSR as main concern, in particular within the retail sector. Retails have close and frequent contact with their customers, which could make the stores vulnerable to poor customers’ relations. By planning on how to present the stores products could be one strong method to communicate to customers the business’ values. To make the most of the values, it is important that the staff share the relevant values. Education can aid in spreading knowledge and values, which often result in engaged employees. Increased knowledge does often lead to the staff get more engaged on the issue and that does often lead to increased productivity. The company may not have relevant in-house capacity and partnership with an NGO may bring in the expertise. The partnership could strive to create shared value by bringing out economic value through societal progress. The thesis is based on a commission from KRAV and is carried out in collaboration with ICA. KRAV’s idea is that environmental education to employees increases the sales of organic products. The aim of the project is to explain and describe the short-term effects of an NGO’s education to food retail staff, in a public-private partnership. To understand and gather information of the phenomenon, several types of data sources were used: observations and interviews before and after the education of ICA personnel, evaluation questionnaires after the educational sessions and sales data from the participating stores. The data were analysed to assess if the attitude towards KRAV and organic production had changed due to the education and if so, had it affected the promotion and sales of KRAV-labelled food in the participating ICA Kvantum stores. The findings show that the education to a high degree change the participants attitudes to organic production and KRAV, and some degree contributes to changed shopping behaviour of the employees. The visual promotion in the stores increased in many of the stores but the employees did not report any significant change in face-to-face promotion to customers. The sales of organic production had a weak correlation to the education of the staff. Changes in habits and culture are assumed to take time, therefore is an evaluation of long-term effects to recommend.